Development of Technology Adoption on Purchase Decisions Among Shopee User - Sari, Tarista Indah Laila; Respatiningtiyas, Dyah Suswanti; Bawono, Muhammad; Arintowati, Dyan (Universitas Nusantara PGRI Kediri, 2025)
Research Aim : This study aims to identify the technology adoption factors that influence purchase decisions among Shopee users. Method: This study employs a quantitative methodology incorporating causality techniques. The population in this study is the community of Gejagan Village, Loceret District, Nganjuk Regency. The sampling technique used the Slovin formula with 358 respondents. The data analysis method used is multiple linear regression Results: The results show that technology adoption factors have an effect on purchase decisions among Shopee users in the community of Gejagan Village, Loceret District, Nganjuk Regency. Keywords : Theory Acceptance Model (TAM), perceived usefulness, ease of use, trust, and buying decision